Perceptions of Teacher Candidates regarding Project-Based Learning - Baysura, Ozge Deniz; Altun, Sertel; Yucel-Toy, Banu (ANI YAYINCILIK, 2016)
Problem Statement. Project-based learning (PBL) is a learning and teaching approach that makes students search for new knowledge and skills, helps them overcome real-life questions, and makes them design their own studies and performances. Research in Turkey reveals that teachers are not well-informed about PBL, can not guide students in this process, and have problems in implementing PBL. This situation raises questions on the effectiveness of teacher education and pedagogical courses in the attainment of knowledge and skills on PBL. Thus, it is important to examine teacher candidates' perceptions regarding PBL during their teacher education. Purpose of Study. The purpose of this study was to investigate teacher candidates' perceptions about the PBL approach in terms of different variables. In this direction, the research question has been specified as 'What are the perceptions of teacher candidates toward PBL?' Methods. It was a qualitative phenomenological study. The research group consisted of 58 students (40 female, 18 male), who were in their third and fourth years in a public university in Istanbul in the 2014-2015 academic year. In order to gather data, open-ended questions were asked. The data were analyzed using content analysis. Findings and Results. According to the findings, more than half of the teacher candidates expressed that they learned PBL approach in theory, but almost half said that they did not have the opportunity to apply it. None of them produced an exact definition of the PBL approach but referred to different aspects of it. Moreover, they mentioned that they will use the PBL approach after graduation. They had a positive attitude to this approach, and they believed that it is a useful approach in developing skills such as doing research, group work, and productivity. Conclusions and recommendations. The results of the research show that teacher candidates are familiar with the PBL approach, but their lack of skills and knowledge in managing it might cause them to have difficulties during their implementation process. In order to equip them with the required skills and information, more space should be left to PBL practices in their pedagogical courses so as to provide opportunities for them to use and apply this approach. In further research, a pedagogical course can be designed according to PBL, and its impact on teacher candidates can be investigated.
Keywords: project-based learning; teacher candidate; teacher education; qualitative research; Education & Educational Research